Direct laser writing of depressed-cladding waveguides in extremely low expansion lithium aluminosilicate glass-ceramics. (June 2021) - Lipatiev, Alexey; Fedotov, Sergey; Lotarev, Sergey; Naumov, Andrey; Lipateva, Tatiana; Savinkov, Vitaly; Shakhgildyan, Georgiy; Sigaev, Vladimir
Highlights: Depressed-cladding waveguides were laser-inscribed in low expansion glass-ceramics. Femtosecond laser-induced vitrification provides reducing the refractive index. Refractive index change in the depressed cladding is stable up to 600 °C. The propagation losses in the fabricated single-mode waveguide are 2.4 dB/cm. Abstract: We report on direct femtosecond laser writing of depressed-cladding optical waveguides in extremely low expansion lithium aluminosilicate glass-ceramics. The waveguide cladding was formed by space-selective vitrification of nanocrystals in laser-modified regions of glass-ceramics responsible for the negative refractive index change up to 0.005. The optical properties of the laser-written waveguides were evaluated in terms of near-field and far-field intensity distribution and propagation losses at the wavelength of 1064 nm. The possibility of single-mode waveguiding with the upper limit of propagation losses 2.4 or 2.7 dB/cm for vertically or horizontally polarized light, respectively, was demonstrated. The obtained results open up new frontiers in the laser-assisted fabrication of 3D optical waveguide circuits in the media with outstanding thermal stability.